Efeitos do esforço prévio de alta intensidade no desempenho técnico-tático em jogadores de basquetebol universitário - Jesus, Carla Souza de (2017)
BACKGROUND:Basketball has intensive and intermittent efforts, however, is unclear, in which they compose affect technical-tactical performance. AIM: To comparethe technical-tactical performance after the high-intensity effort in college basketball players. METHODS:Ten male college basketball team athletes performed warm-up (5 min), followed or not from the Super-7 exercise, on different days. Shortly thereafter, the athletes performed two simulated 5v5 games lasting 10 min on different days:Light Pré-exercise Game (LGAME) vs. Vigorous Préexercise Game (VIGAME). A rating perception of effort for recordaded in the procedures and the internal load of the games was calculate. The technicaltactical performance was evaluate by: IAD-BB, and Basic and Advanced Game Statistics. The data of the athletes were groupedfor comparison between the simulated games.RESULTS: The RPE in the warm-ups were equivalent and VIGAME presented higher value for the LGAME (7.6 ± 1.1 and 5.7 ± 1.3 u.a.). There was no difference in overall technical-tactical performance according to specific IAD-BB components. During VIGAME there were fewer 3 point shots, assists, turnovers, field goal %, successful fastbreaks, points in the paint, drives, catch-and-shoot shots, lay-up %, field goals attempt, defensive rebounds. CONCLUSIONS:The high intensity pre-exercise did not influence the technicaltactical performance of basketball players. However,there was changing in the quality of the actions observed in the game statistics.